An Exploration of Early Childhood Teachers' Technology, Pedagogy, and Content Knowledge (TPACK) in Mainland China. Issue 4 (19th May 2023) - Luo, Wenwei; Berson, Ilene R.; Berson, Michael J.; Park, Sanghoon
ABSTRACT: Research Findings: This study aims to validate a scale highlighting the applicability of selected TPACK (Technological Pedagogical Content Knowledge) domains of knowledge to early childhood education and to explore the internal relationships between TPACK's components in the Chinese context. A survey instrument was designed and administered to 1, 192 early childhood (EC) in-service teachers enrolled in their national training programs. The instrument consisted of 29 items classified into four categories that align with the conceptual TPACK framework and are applicable to the EC context, including Technology Knowledge (TK), Technological Pedagogical Knowledge (TPK), Pedagogical Knowledge (PK), and TPACK. CFA and path analysis generated a model with good fit. The confirmed model indicated that (1) TK, TPK, and PK were significantly correlated; (2) TK, TPK, and PK all had direct positive effects on TPACK; however, (3) PK had a smaller influence on TPACK. Practice or Policy: The instrument was a reliable and valid assessment for measuring the TPACK of Chinese EC teachers and may be used to inform future research. The findings suggest that ECE training should shift away from focusing on discrete technological skills (i.e., TK) and instead emphasize preparing teachers with mastery in pedagogic approaches for integrating digital technology into instruction.